Influence of Microalloying Process on Dynamic Mechanical Relaxation of ZrCo-Based Amorphous Alloy - Rosario Mireya Romero Parra; Indrajit Patra; Fatima Safaa Fahim; Samar Emad Izzat; Ali Thaeer Hammid; Saeed Razavinejad (Advances in Materials Science and Engineering)
In this study, the dynamic mechanical spectroscopy was used to characterize the effects of minor Ni addition on the relaxation behavior of ZrCoAl bulk metallic glass (BMG). For this purpose, the Kohlrausch–Williams–Watts (KWW) function and quasi-point defect (QPD) model were used for evaluation of relaxation under the different aging temperatures. The results indicated that the Ni addition shifted the relaxation process to the higher temperatures. Moreover, the estimations showed that the activation energy of relaxation was 5.951 eV and 6.205 eV for ZrCoAl and ZrCoAlNi, respectively. It was also revealed that the microalloying process enhanced the structural defects in the system and led to the improvement of dynamic heterogeneity in the BMG. Comparing the physical models, it is suggested that a small change in the structural defects intensifies the dynamic heterogeneity in the material.